2015
DOI: 10.1016/j.coph.2014.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between (Pro)renin receptor and COX-2 in the renal medulla during angiotensin II-induced hypertension

Abstract: Angiotensin II (AngII) is an octapeptide hormone that plays a central role in regulation of sodium balance, plasma volume, and blood pressure. Its role in the pathogenesis of hypertension is highlighted by the wide use of inhibitors of the renin-angiotensin system (RAS) as the first-line antihypertensive therapy. However, despite intensive investigation, the mechanism of AngII-induced hypertension is still incompletely understood. Although diverse pathways are likely involved, increasing evidence suggests that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 63 publications
1
18
1
Order By: Relevance
“…Also, our results found that the inhibition of AngII and COX2 blocked RIIH-induced PRR expression, which confirmed the essential roles of AngII and COX2 in increasing renal PRR expression during RIIH. Previous studies documented that COX2/PGE2/EP4 pathway is responsible for high PRR expression in the renal medulla during AngII-induced hypertension (Green et al 2012, Wang et al 2014, Yang 2015. However, in the current study, RIIH induced AngII which might activate the COX2/PGE2/EP4 pathway and lead to an increase in expression of PRR in the kidney.…”
Section: Discussioncontrasting
confidence: 47%
“…Also, our results found that the inhibition of AngII and COX2 blocked RIIH-induced PRR expression, which confirmed the essential roles of AngII and COX2 in increasing renal PRR expression during RIIH. Previous studies documented that COX2/PGE2/EP4 pathway is responsible for high PRR expression in the renal medulla during AngII-induced hypertension (Green et al 2012, Wang et al 2014, Yang 2015. However, in the current study, RIIH induced AngII which might activate the COX2/PGE2/EP4 pathway and lead to an increase in expression of PRR in the kidney.…”
Section: Discussioncontrasting
confidence: 47%
“…In vitro and in vivo results suggested a crucial role of COX-2 in mediating upregulation of renal medullary (pro)renin receptor (PRR) expression and rennin content during ANG II-induced hypertension. (18, 61). Our subsequent study further claimed that the specific COX-2/PGE 2 /EP 4 pathway mediated the upregulation of renal medullary PRR expression by ANGII, leading to activation of intrarenal RAS and enhancement of the hypertensive response (62).…”
Section: Discussionmentioning
confidence: 99%
“…The goal of this review to summarize the major findings in the literature concerning the regulation and function of renal medullary COX-2 during high salt loading. For general knowledge about renal PG pathway, you are referred to a number of previous review articles (9, 1618). …”
Section: Introductionmentioning
confidence: 99%
“…Li, et al, 2015), and a cyclooxygenase (COX)-2–dependent pathway in the kidney (Wang, et al, 2014). Increased PRR expression may further promote the production of Ang II, ultimately resulting in positive feedback regulation of the receptor itself and the development of hypertension (Wang, et al, 2014; T. Yang, 2015).…”
Section: Introductionmentioning
confidence: 99%